Critical Discourse Analysis Of Joe Biden's Speech After Donald Trump's Victory: A Van Dijk Perspective - Eka Susylowati; Nisrina Salma Octaviana (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2026)
The study investigates how discourse constructs ideology and power relations through textual and social dimensions. This study employs critical discourse analysis through Van Dijk's (2008) framework to examine Joe Biden's speech after Donald Trump's 2024 presidential victory. Through macrostructure, his speech demonstrated the tenacity of democracy and the importance of collective responsibility. The main message of his speech was inclusiveness and faith in the democratic process and to appeal for Americans to come together no matter where they stand on a political differences. The method used in this study is a qualitative descriptive method based on Van Dijk's (2008) theory. This analysis uses Van Dijk's (2008) three-dimensional model that includes macrostructure, superstructure, and microstructure. This study investigates how Biden's discourse legitimized the electoral process, bridged political divisions, and influenced public narratives. The results reveal how Biden strategically uses language to promote unity, trust in democratic institutions, and peaceful transition, highlighting the power of political discourse in navigating difficult times. It is contributes to understanding the role of presidential communication in shaping national narratives and managing social cohesion during political transitions. The study contributes to discourse analysis by demonstrating how Van Dijk’s model can reveal hidden ideologies in language and highlight the relationship between discourse and social power.